THE EVALUATION OF HOPELESSNESS AND PERCEIVED SOCIAL SUPPORT LEVEL IN PATIENTS WITH LUNG CANCER - Yesilot, Saliha Bozdogan; Oztunc, Gursel; Demirci, Pınar Yesil; Manav, Ayse Inel; Paydas, Semra (LIFE: International Journal of Health and Life-Sciences, 2017)
Lung cancer is most common and a leading cause of death in women and men in the worldwide. It has multidimensional effects on patients and their families. Aim of this study was to evaluate level of hopelessness and perceived social support in patients with lung cancer. This cross-sectional and descriptive study carried out in oncology outpatient unit of a university hospital in Adana, Turkey. The research sample consisted of 98 patients who have been treated between March 1, 2016 and August 31, 2016, have diagnosed lung cancer at least 3 months ago, have cognitive competence to answer questions and volunteer to join the study. Data were collected with socio-demografic form, Beck Hopelessness Scale and Multidimensional Scale of Perceived Social Support. Analysis was made using by descriptive statistical methods (means, standard deviation, frequences), Mann-Whitney U Test, Kruskall-Wallis H test and Spearman Corelation coeffitient test. Statistical significance was taken as p<0,05.Mean age of the participants was 58,34±9,31. In all, 87.8% was male, 80.6% was married, 91.8% had children. The mean scores of scale was respectively;Beck Hopelessness Scale was 5,84±3,55 (lower level) and Multidimensional Scale of Perceived Social Support was 65,24±14,74 (high level). There was no statistically significant relationship between total scores of Beck Hopelessness Scale and Multidimensional Scale of Perceived Social Support. It was found that there was a statistically significant relationship between total scores of hopelessness and having social security, and also total scores of Perceived Social Support Scale with marital status (p<0.05).Our findings indicate that patients with lung cancer have high level social support, mild level hopelessness. Social support can be a protective factor for hopelessness. Therefore ıt is suggested that social support systems can make stronger to increase hope level of patients.